Screening parameters for diagnosing primary aldosteronism in patients with moderate to severe obstructive sleep apnea hypopnea syndrome and resistant hypertension - Yan, Dien; Zou, Xiaofan; Li, Xiao; Zeng, Qiao; He, Hongbing; Guo, Jianping; Wang, Yulan; Zheng, Huanhuan; Fu, Jinxiang; Wang, Meili; Peng, Danping; Zhou, Xiaozi; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Patients with obstructive sleep apnea hypopnea syndrome (OSAHS) combined with resistant hypertension (RH) have a high risk of developing primary aldosteronism (PA). This study investigated the aldosterone-renin ratio (ARR), plasma aldosterone concentration (PAC), and plasma renin activity (PRA) to determine the optimal cutoff values for PA diagnosis in patients with OSAHS combined with RH. Methods Patients diagnosed with moderate and severe OSAHS combined with RH were recruited from the inpatient clinic of the Department of Endocrinology at Ji'an Central Hospital between October 2020 and April 2023. The included patients were divided into PA and no-PA groups. Diagnostic accuracy measures were calculated for each group, and receiver operating characteristic (ROC) curves were generated. Results A total of 241 patients were included, of which 103 had positive ARR screening results in the diagnostic accuracy analysis and 66 were diagnosed with PA. PAC and ARR showed moderate predictive capacity for PA, with area under the curve (AUC) values of 0.66 [95% confidence interval (CI): 0.55–0.77] and 0.72 (95% CI: 0.63–0.82), respectively, while PRA exhibited a limited predictive capacity (AUC = 0.51, 95% CI: 0.40–0.63). Using 45 as the optimal cutoff value for ARR, the sensitivity was 86% and the specificity was 52%. The optimal cutoff value for PAC was 17, with a sensitivity of 78% and a specificity of 55%. Notably, in patients with severe OSAHS, ARR at screening demonstrated significant predictive value for PA, with an AUC of 0.84 (95% CI: 0.72–0.96), a sensitivity of 85%, and a specificity of 76%. Conversely, in patients with moderate OSAHS, only ARR demonstrated significant predictive value for PA diagnosis, while PAC did not demonstrate notable diagnostic value. Conclusion ARR and PAC are initial screening tools for PA, facilitating early detection, particularly in low-resource settings. In patients with OSAHS and RH, the ARR and PAC thresholds for PA diagnosis may require more stringent adjustment.